The Impact of The Crime of Terrorism on World Security in International Law Perspective - Miliarni Deida Navydien; Shafira Tri Pinareswati; Khesya Khusnul Fadhilah Utomo; Ramadhani, Annisa Amalia (Academos, 2023)
Terrorism is a form of crime that is included in the extraordinary crime which in its legal settlement requires special handling. The crime of terrorism is a crime that is feared by the world community, including Indonesia, because the characteristics of this crime are to create a sense of insecurity and spread terror to society and the victims of this crime of terrorism feel that until now they have not received full justice. The writing of this law is a normative legal research using the literature study method to resolve legal issues related to the impact of terrorism on security in the perspective of international law which is then analyzed using related laws and regulations. The result of writing this law is the need for protection and a sense of justice for victims of criminal acts of terrorism and also the role of law enforcers is needed to uphold justice and the role of the government in terms of being able to provide fair compensation for victims affected by acts of terrorism.